Pengaruh Konsumsi Air Kelapa Terhadap Pengurangan Nyeri Haid (Dismenorea) - Nuryanih M.kep.,Sp.Kep.Mat; Suhatika (Sekolah Tinggi Ilmu Kesehatan Yatsi, 2020)
ABSTRACT Background: Green coconut water is a healthy drink that is rich in nutrients, vitamins and minerals and naturally without preservatives, green coconut water is easily absorbed by the body because of isotomic fluid content with the human body Menstrual pain (Disminore). Research Objectives: To determine the relationship of consuming green coconut water by reducing menstrual pain (Diminore) on STIkes YATSI Tangerang students. Research Methods: This research is quantitative with a descriptive correlation design using a cross sectional approach. The researcher begins with the selection of respondents who meet the inclusion criteria. The researcher uses random sampling with 82 respondents, the data uses the Chi-Square test. Research Results: From the results of this study show a bivariate analysis using the chi-square test results obtained statistically that the significant value is 0,000 ( 0,000 <0.05) It means that there is a relationship between consuming coconut milk with reducing menstrual pain (Desminore) in Level 1 nursing students in Yatsi Stikes Tangerang in 2019. Conclusions and Recommendations: Based on the research results there is a significant relationship between consuming green coconut water by reducing Menstrual pain (Desminore) at Level 1 Students of Stikes Yatsi Tangerang. It is recommended to consume green coconut water and can be used to reduce menstrual pain (Desminore) in a non-pharmacological manner.